2021
DOI: 10.1155/2021/1839399
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Efficacy of Standard-Dose versus Low-Dose Non-Vitamin K Antagonist Oral Anticoagulants in Patients with Nonvalvular Atrial Fibrillation and Left Atrial Appendage Thrombus

Abstract: Background. Data comparing different doses of non-vitamin K antagonist oral anticoagulants (NOACs) regarding resolution of left atrial appendage thrombus (LAAT) in patients with nonvalvular atrial fibrillation (AF) are scarce. This study aimed to investigate the safety and efficacy of standard-dose versus low-dose NOACs in patients with nonvalvular AF and LAAT. Methods. Patients with nonvalvular AF who underwent transesophageal echocardiography (TEE) before interventional procedures for the detection of LAAT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
1
1
Order By: Relevance
“…Short-term OAC, including NOACs and VKA, has long been used to resolve LAAT or sludge in patients with NVAF. Previous studies investigating the efficacy of NOACs or AVK showed conflicting results with the resolution rate of LAAT ranging from 41.5-85.7% [14,[20][21][22][23][24]. However, in the present study, all LAATs or sludges effectively resolved after OAC medication of 3-4 months, whether standard-dose NOAC, reduceddose NOAC or VKA (TTR ranging from 60 to 75%).…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Short-term OAC, including NOACs and VKA, has long been used to resolve LAAT or sludge in patients with NVAF. Previous studies investigating the efficacy of NOACs or AVK showed conflicting results with the resolution rate of LAAT ranging from 41.5-85.7% [14,[20][21][22][23][24]. However, in the present study, all LAATs or sludges effectively resolved after OAC medication of 3-4 months, whether standard-dose NOAC, reduceddose NOAC or VKA (TTR ranging from 60 to 75%).…”
Section: Discussioncontrasting
confidence: 72%
“…Previous study demonstrated that the patients with LAAT resolution had lower CHA 2 DS 2 -VASc scores [22]. In addition, the overall resolution rate is obviously higher in the Asian race [22][23][24]. The racial disparity of effectiveness and safety with OAC has been discussed in various studies.…”
Section: Discussionmentioning
confidence: 99%